Antimicrobial Potential and Molecular Characterisation of Endophytic Fungi Isolated from Conyza bonariensis from Tanzania - Simeon Phares Nsindagi; Cyprian Beda Mpinda; Fulgence Ntangere Mpenda (Turkish Journal of Bioscience and Collections)
Objective: The harnessing of medicinal plants for the treatment of infectious diseases has an environmental concern, and therefore environmentally friendly alternative sources like harnessing the potential of endophytes are of paramount importance. The present study aimed to evaluate chemical composition and antimicrobial activity of crude extracts of endophytic fungi isolated from C. bonariensis (L.) in Tanzania.Materials and Methods: Initially, endophytic fungi were isolated from C. bonariensis (L.) and characterized, followed by mass cultivation and the harvesting of crude extracts. Then crude extracts were tested against selected microorganisms: Two Gram-positive bacteria, Staphylococcus aureus and Bacillus subtilis; Two Gram-negative bacteria, Escherichia coli and Salmonella typhi, and a yeast Candida albicans. Gas Chromatography-Mass Spectrometry analyzed the chemical composition of crude extracts.Results: Five endophytic fungi (Talaromyces sp., Penicillium daleae, Neurospora crassa, Talaromyces radicus 1 and Talaromyces radicus 2) were isolated. Furthermore, crude extract of N. crassa had the highest antimicrobial activity with the range of MIC found to be 1.5 μg/mL > MIC > 0.78 μg/mL for all tested microorganisms except for S. aureus where the range of MIC was 40 μg/mL>MIC>20 μg/mL. On the other hand, the crude extract of Talaromyces radicus 1 had the lowest MIC range (100 mg/mL>MIC>50 mg/mL). The GC-MS results demonstrated variation in chemical composition with proved various biological properties.Conclusions: Ethyl acetate crude extracts of N. crassa demonstrated the highest antimicrobial activity, therefore warranting further exploration of the endophyte and their crude extracts for various medicinal and industrial applications. Further studies on the characterization of pure compounds, which may be responsible for the antimicrobial activity that was observed, are urgently needed.